Nucleus pulposus cell-matrix interactions with laminins - CL Gilchrist; AT Francisco; GE Plopper; J Chen; LA Setton (European Cells & Materials, 2011)
The cells of the nucleus pulposus (NP) region of the intervertebral disc play a critical role in this tissue’s generation and maintenance, and alterations in NP cell viability, metabolism, and phenotype with aging may be key contributors to progressive disc degeneration. Relatively little is understood about the phenotype of NP cells, including their cell-matrix interactions which may modulate phenotype and survival. Our previous work has identified strong and region-specific expression of laminins and laminin cell-surface receptors in immature NP tissues, suggesting laminin cell-matrix interactions are uniquely important to the biology of NP cells. Whether these observed tissue-level laminin expression patterns reflect functional adhesion behaviors for these cells is not known. In this study, we examined NP cell-matrix interactions with specific matrix ligands, including various laminin isoforms, using quantitative assays of cell attachment, spreading, and adhesion strength. NP cells were found to attach in higher numbers and exhibited rapid cell spreading and higher resistance to detachment force on two laminin isoforms (LM-511,LM-332) identified to be uniquely expressed in the NP region, as compared to another laminin isoform (LM-111) and several other matrix ligands (collagen, fibronectin). Additionally, NP cells were found to attach in higher numbers to laminins as compared to cells isolated from the disc’s annulus fibrosus region. These findings confirm that laminin and laminin receptor expression documented in NP tissues translates into unique functional NP cell adhesion behaviors that may be useful tools for in vitro cell culture and biomaterials that support NP cells.